ANALISIS EFEKTIVITAS PENGENDALIAN INTERN ATAS SISTEM PEMBERIAN DAN PELUNASAN KREDIT GADAI - Meiriza Riyandini; Ahmad Subeki; Aryanto Aryanto (AKUNTABILITAS, 2013)
The purpose of this study was to determine the effectiveness of internal control over the system of giving and paying off mortgage credit at PT. Pegadaian (Persero) Palembang Pallima Branch Office. And to find out the cause of the decline in the number of customers at PT. Pegadaian (Persero) Pallima Palembang Branch Office in 2010-2013 and its effect on performance effectiveness at PT. Pegadaian (Persero) Palembang Pallima Branch Office.This research is a qualitative descriptive study. The type of data used in this study are primary data and secondary data. The data used is the percentage data and customer classification, income data, loan amount data, and operational standards (SOP) at PT. Pegadaian (Persero) Palembang Pallima Branch Office. The method of analysis is by paying attention to the elements of internal control, namely the internal control environment, risk assessment, control activities, and information and communication.The results of the analysis and research show that internal control over the system of giving and paying off mortgage credit at PT. Pegadaian (Persero) Palembang Pallima Branch Office is quite effective because it has been in accordance with established procedures. In addition, the decline in the number of customers in 2010-2013 did not have a negative impact on the performance of PT. Pegadaian (Persero) Palembang Pallima Branch Office which can be seen at PT. Pegadaian (Persero) Palembang Pallima Branch Office which is increasing every year.